STRATEGI MENINGKATKAN KEPUASAN PELANGGAN PADA TOKO OBAT HASAN PALEMBANG - Apriyanti, Berliana; Widagdo, Herry (Universitas Multi Data Palembang, 2023)
This study aims to analyze the effect of Product Diversity, Location, Word of Mouth (WOM) and price on customer satisfaction of Hasan Drug Store in Palembang partially or simultaneously. In this study, the method used was quantitative, and the type of research used was descriptive analysis with data collection techniques with a total sample of 150 respondents. The results of the study obtained the results of a significant influence that has been carried out regarding the discussion of the influence of Product Diversity, Location, Word of Mouth (WOM) and price on customer satisfaction of Hasan Drug Store in Palembang which has been discussed in the previous section, the conclusion in this study is the results of the research variables Product Diversity, Location, Word of Mouth (WOM) and price simultaneously have a positive and significant effect on customer satisfaction of Hasan Drug Store in Palembang.